[PP.19.01] PREVALENCE AND RISK FACTORS RELATED TO DEVELOPMENT OF ARTERIAL HYPERTENSION IN CIRRHOTIC PATIENTS UNDERGOING LIVER TRANSPLANTATION. (September 2016) - Di Stefano, C.; Vanni, E.; Mirabella, S.; Jouness, R. Ibrahim Kamal; Nada, E.; Boano, V.; Mosso, E.; Milazzo, V.; Vallelonga, F.; Sobrero, G.; Salizzoni, M.; Veglio, F.; et al.
Abstract : Objective: The prevalence of arterial hypertension after orthotopic liver transplantation (OLT) is estimated between 31–82%, and may represent a common complication of immunosuppressive therapy. The aim of this study is to evaluate the prevalence of arterial hypertension after immunosuppressive therapy for OLT. Design and method: From a cohort of cirrhotic patients undergone OLT from 2008–2012, 270 patients with at least 24-months follow-up visits were evaluated. Hypertension was defined as clinical blood pressure >=140/90 mmHg in at least two visits and/or presence of therapy with antihypertensive effects. We retrospectively analyzed main anthropometric variables, etiology and severity of liver disease, metabolic comorbidities and type of immunosuppressive drugs (cyclosporine, tacrolimus, corticosteroids, mycophenolate mofetil, and mammalian target of rapamycin inhibitors - mTORi) potentially related to arterial hypertension development. Results: 24.1% of patients were women and the mean age was 53.4 ± 9.3 years. The mean follow-up was 43 ± 19 months after OLT. The prevalence of hypertension was 15.2% before OLT (n. 49) and increased up to 53% (n. 143) after OLT. Excluding 'chronic' hypertensive subjects (n. 25, 9.3%), 30.9% of normotensive subjects (n. 83) developed persistent hypertension after OLT, while 13% (n. 35) developed hypertension only within one month after OLT, subsequently returning normotensive. The development of persistent hypertension after OLT was related to mTORi (OR 4.02, 95% CI 1.26–13.48, p = 0.02), alcoholic cirrhosis before OLT (OR 3.38, 95% CI 1.44–8.09, p = 0.005), and development of hepatic steatosis after OLT (OR 2.13, 95% CI 1.10–4.11, p = 0.02). Patients with 'acute' hypertension were more often affected from hepatitis C virus cirrhosis (p = 0.03). The etiology (including NASH disease) and the severity of liver disease, and other immunosuppressive regimens (including cyclosporine and corticosteroids) were not related to the development of hypertension after OLT. Conclusions: The prevalence of arterial hypertension increases from 15% to 53% after OLT. Metabolic comorbidities and immunosuppressive treatment with mTORi seems to be associated with the development of hypertension after OLT in previously normotensive subjects.